Complementary and Alternative Medicine Providers in Rural Locations - Elizabeth Nichols; Clarann Weinert; Jean Shreffler Grant; Bette Ide (Rural Nurse Organization; Binghamton University, 2012)
The purpose of this study was to determine the availability of complementary and alternative medicine (CAM) resources to individuals in twenty rural communities in two western states and to ascertain the contribution of one type of CAM provider, naturopathic physicians, to rural health care. Resource data were collected through internet phone directories searches and an on-line survey of Montana naturopaths. Seventy-three CAM providers were identified in the target communities. The naturopathic physician's practices were located in urbanized areas of Montana, some with outreach clinics. Most naturopaths made regular referrals to conventional medical practitioners; however few received referrals. Comparison of use patterns of CAM by older residents of these communities to the presence of providers in the communities suggests that local availability is not the critical factor in use of a CAM therapist or self-directed therapy.